Variation of suspended sediment transport in the Timah Tasoh Reservoir catchment, Perlis, Malaysia : human impacts and the role of tropical storms - Zullyadini, A. Rahaman; Wan Ruslan, Ismail (2006)
In recent years, soil erosion, sediment transport and deterioration of water quality in many river systems in Malaysia have become major concerns. Headwater streams emanating from forested and agricultural lands supply much of the potable water in this country. The quality, quantity and timing of water from these headwater catchments are strongly influenced by human activities such as deforestation associated with land conversion for agricultural purposes. This study investigates the impact of human acitivities and the role of tropical storms on the variation of sediment transported into the Timah tasoh Reservoir, Perlis, Malaysia.